New developments in intrauterine device use: focus on the US - Nelson AL; Massoudi N (Dove Medical Press, 2016)
Anita L Nelson,1 Natasha Massoudi2 1Department of Obstetrics and Gynecology, Los Angeles BioMedical Research Institute at Harbor-UCLA Medical Center, David Geffen School of Medicine at UCLA, Torrance, CA, USA; 2American University of the Caribbean School of Medicine, Cupecoy, Sint Maarten Abstract: Many more women in the US today rely upon intrauterine devices (IUDs) than in the past. This increased utilization may have substantially contributed to the decline in the percentage of unintended pregnancies in the US. Evidence-based practices have increased the number of women who are medically eligible for IUDs and have enabled more rapid access to the methods. Many women enjoy freedom to use IUDs without cost, but for many the impact of the Affordable Care Act has yet to be realized. Currently, there are three hormonal IUDs and one copper IUD available in the US. Each IUD is extremely effective, convenient, and safe. The newer IUDs have been tested in populations not usually included in clinical trials and provide reassuring answers to older concerns about IUD use in these women, including information about expulsion, infection, and discontinuation. On the other hand, larger surveillance studies have provided new estimates about the risks of complications such as perforation, especially in postpartum and breastfeeding women. This article summarizes significant features of each IUD and provides a summary of the differences to aid clinicians in the US and other countries in advising women about IUD choices. Keywords: copper intrauterine device, levonorgestrel intrauterine systems, noncontraceptive benefits, same-day/quick start initiation, safety, bleeding patterns, placement pain, medical eligibility